Chemometric tools for the characterisation of honey produced in La Pampa, Argentina, from their elemental content, using inductively coupled plasma optical emission spectrometry (ICP-OES) - Camiña, José Manuel (2008)
Thirty two samples of natural honey produced in the province of La Pampa (Argentina) were characterised on the basis of their phosphorous, aluminium, iron, calcium, magnesium and sodium contents. Analytical determinations were carried out using inductive coupled plasma optical emission spectrometry (ICP-OES). For characterisation, chemometric methods used were Principal Components Analysis (PCA) and Cluster Analysis (CA), while for classification, Linear Discriminant Analysis (LDA) was used. The results show that samples obtained within 50 km from the centre of the province (around Santa Rosa, the capital city), were different from those coming from the rest of the province, generating a classification based on geographical origin. Phosphorous content was the most significant variable in the classification of the PCA model.